Oscillation criteria for second-order quasilinear neutral functional dynamic equation on time scales - Saker, S.H. (Нелінійні коливання, 2010)
Our aim in this paper is to esatblish some sufficent conditions for oscillation of the second-order quasilinear neutral functional dynamic equation. Some examples are considered to illustrate the main results.